Neoliberalism and right-wing populism: Conceptual analogies - Stephan Pühringer; Walter Ötsch (Cusanus Hochschule, Institut für Ökonomie und Institut für Philosophie, 2017)
The paper compares neoliberal market-fundamentalism and right-wing populism on the basis of its core patterns of thinking and reasoning. Hence we offer an analysis of the work of important founders of market-fundamental economic thinking (particularly von Mises) and an established definition of populism (demonstrated by the example of arguments brought forward by leading populists, like Trump). In doing so, we highlight conceptual resemblances of these two approaches: Both assume a dually divided world that is split into only two countervailing parts. Right-wing populism shows a society split into two groups, fighting against each other. In a similar vein, neoliberal market-fundamentalists argue that there are only two possible countervailing economic and societal orders. We argue that the categorical analogies between neoliberal marketfundamentalism and right-wing populism could provide the basis for a new form of authoritarian neoliberalism.
Keywords: B19; E50; E61; E65; G18; G38; Z18; 330; right-wing populism; market-fundamentalism; Ludwig von Mises; Donald Trump; patterns of thinking